A Circular Economy-Based Strategy for the Development of Biochar from Oil Palm Empty Fruit Bunches to Increase Added Value at PT Perkebunan Nusantara IV - Wijayanto, Setyo Dwi; Nazaruddin, Nazaruddin; Sembiring , Meilita Tryana (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to formulate a strategy for developing biochar from empty fruit bunches (EFB) waste based on a circular economy approach to increase the added value of PT Perkebunan Nusantara IV. As a large-scale palm oil plantation company, PTPN IV generates a significant volume of EFB from fresh fruit bunch processing. Current EFB utilization is still dominated by land application, incineration, and direct selling, which have not yet created optimal economic value for the company. This research applied a case study approach supported by qualitative and quantitative analysis through document review, interviews, limited observation, cost-benefit analysis, value-added analysis, risk analysis, and strategy formulation using SWOT and TOWS frameworks. The findings indicate that converting EFB into biochar has the potential to transform waste from a cost center into a value driver by reducing waste handling costs, partially substituting chemical fertilizer use, creating commercialization opportunities, and strengthening the company’s environmental and ESG performance. Biochar development also supports the implementation of a closed-loop supply chain between palm oil mills and plantations, making it consistent with circular economy principles. The recommended implementation strategy includes conducting a pilot project, developing standard operating procedures and quality standards, strengthening human resource capacity, establishing technology partnerships, conducting agronomic validation, and implementing the program gradually in operational units with the highest readiness. Therefore, EFB-based biochar development can serve as a sustainable business strategy that supports operational efficiency, downstream development, and added value creation for PTPN IV.